Unusual splenic sinusoidal iron overload in sickle cell/haemoglobin D-Punjab disease. Issue 5 (27th April 2004) - Jiskoot, P M C; Halsey, C; Rivers, R; Bain, B J; Wilkins, B S
Abstract : Sickle cell/haemoglobin D-Punjab disease is a disorder with similar clinical features to sickle cell anaemia. This report describes the case of an 11 year old boy with this disease who was treated with regular transfusions from infancy. He underwent splenectomy at the age of 10 years for hypersplenism. Histology of the spleen revealed a striking pattern of heavy sinusoidal endothelial iron loading, with only moderate uptake by macrophages. Possible explanations for this unusual distribution of iron include phagocytosis of sickled erythrocytes by sinusoidal endothelial cells or direct endothelial iron uptake via transferrin receptors. Transfusion programmes ameliorate the symptoms of sickle cell disease but the dangers of iron overload should always be remembered.